Development of Pyrimidine-metabolizing Enzymes in Cotyledons of Germinating Peas - Ross, Cleon (1971)
Mechanisms controlling conversion of orotic acid-6-(14)C to uridine-5′-phosphate in cotyledons of germinating Alaska peas (Pisum sativum L.) were investigated. The content of 5-phosphoribosyl-1-pyrophosphate was very low in dry seeds, increased to a maximum after about 12 hours of imbibition, and then rapidly declined. Orotidine-5′-phosphate pyrophosphorylase and orotidine-5′-phosphate decarboxylase activities more than doubled during the first 24 hours of germination and then also decreased. These results do not account for the continuous increases of orotate anabolism in such cotyledons as we observed previously. The initial increases in activities of these two enzymes were unaffected by cycloheximide, while the subsequent decreases were less rapid in the presence of this inhibitor. Activities of cotyledonary cytidine deaminase and uridine hydrolase also increased during imbibition, but the activity of only the latter showed a decrease after imbibition was completed. Cycloheximide inhibited the initial rapid increase in uridine hydrolase activity but had little effect on its subsequent decline. Cycloheximide had only slight inhibitory effects on the development of cytidine deaminase activity during the first 62 hours. The evidence suggests that uridine hydrolase might be synthesized de novo during the first few days of germination, but that the other three enzymes might not be.